Ocean Advocacy in Discourse: Unpacking 'Seaspiracy' through an Eco-Critical Lens - Putrianti Viola Novitasari; Galuh Nur Rohmah (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2023)
The decrease in the wildlife population over the last 30 years was caused by various human actions, one of them was triggered by various writings and discourses spread in society. This study aims to analyze the narration of documentary film "Seaspiracy" by Netflix, focusing on the representation of marine destruction. This study examines the representation of marine destruction in the context of texts, discourses, social practices and an ecolinguistic perspective. A qualitative approach was used by combining ecolinguistics (Stibbé, 2015) and Critical Discourse Analysis (Fairclough, 1995, 2003 and 2013) and LSF (Halliday, 2014) to analyze the data in depth. The data used in this study comes from the 2021 documentary "Seaspiracy", produced by Netflix. The research findings reveal linguistic features, including metaphor, irony, and similes. Regarding grammar, humans, marine animals, and the unsustainable fishing industry were found as actors, goals and attributes. However, the highest ratio lies in animals as passive participants and fishing industry players as actors (active participants). The discourse practice shows that between Netflix and Ali Tabrizi shape the audience's perspective and understanding of environmental issues and the fishing industry. In sociocultural practice, this film raises environmental concerns to change public perceptions and encourage positive action in protecting the marine environment. From an ecolinguistic perspective, this study identifies the film "Seaspiracy" as a useful contribution due to its wide dissemination to ensure the sustainability of marine ecosystems. These findings can contribute to understanding how language and discourse shape perceptions and attitudes towards environmental issues.Keywords - Eco-Critical Discourse Analysis, Film Documentary, Transitivity.